PEMAHAMAN MAHASISWA TERHADAP PANDEMI COVID_19 - Arifin, Syamsul; Samodra, Y Touvan Juni; Gustian, Uray (Universitas Tanjungpura, 2023)
This study aims to determine understanding during the covid_19 pandemic using a questionnaire. The sampling technique used is a group sample that is in the WA group of PKO student study programs. Based on the research results obtained from 167 respondents who are included in the WA group of PKO students at Tanjungpura University who filled out a questionnaire of 93 respondents. Percentage statistical data analysis techniques. The results showed that the covid_19 variable in the four alternative answers was obtained in the value range of 63-80%. or included in the high category with a percentage of 73% and two alternative answers obtained in the range of 60% or included in the low category with a percentage of 90%.